Mixed Ligand Complexes of quinoline-2-carboxylic acid and 4,4/-dimethyl-2,2/-bipyridyl with V(IV),Cr(III), Rh(III), Cd(II) and Pt(IV) (Baghdad Science Journal, 2014)
A new mixed ligand complexes were prepared by reaction of quinoline -2-carboxylic acid (L1) and 4,4?dimethyl-2,2?-bipyridyl (L2) with V(IV),Cr(III), Rh(III), Cd(II) and Pt(IV) ions. These complexes were isolated and characterized by (FT-IR) and (UV-Vis) spectroscopy, elemental analysis, flame atomic absorption technique, thermogravimetric analysis, in addition to magnetic susceptibility and conductivity measurements. Most complexes were mononuclear and with octahedral geometry, except Cd (II) with tetrahedral geometry, and V (IV) with square pyramidal geometry. A theoretical treatment of the ligands and the prepared complexes in gas phase was done using two programs Hyperchem.8 and Gaussian program (GaussView Currently Available Versions (5.0.9) along with Gaussian 09 which is the latest in the Gaussian series of programs).